Organization of remote distance learning in the Arctic State Institute of Culture and Art of Yakutia - Gotovtseva, Olga Gerasimovna; Barakhsanov, Vladimir Polikarpovich; Cherkashin, Valentin Valentinovich; Zaikov, Maksim Andreevich; Danilov, Eduard Karlovich (Revista on line de Política e Gestão Educacional, 2021)
This article presents the organization of remote distance learning in Arctic State Institute of Culture and Art (ASICA) of the Republic of Sakha (Yakutia). It shows features of remote distance learning in ASICA based on the use of Moodle distance learning management system. The important thing for the functioning of the digital learning environment is the availability of resources: material and technical, human resources of teachers with formed multimedia competencies in software and modern technologies used. The survey result was shown regarding the availability of information within Moodle environment, which provides all types of classes and procedures for assessing learning outcomes whose implementation envisages the use of e-learning and distance learning technologies. The practical significance of the study lies in the specifics of training students – future professionals of culture and art in the transition to remote distance learning. Este artículo presenta la organización del aprendizaje a distancia en el Instituto Estatal Ártico de Cultura y Arte (ASICA) de la República de Sakha (Yakutia). Muestra las características de la enseñanza a distancia en ASICA basada en el uso del sistema de gestión de la enseñanza a distancia Moodle. Lo importante para el funcionamiento del entorno de aprendizaje digital es la disponibilidad de recursos: materiales y técnicos, recursos humanos de los profesores con competencias multimedia formadas en el software y las tecnologías modernas utilizadas. El resultado de la encuesta se mostró en relación con la disponibilidad de información dentro del entorno Moodle, que proporciona todo tipo de clases y procedimientos para evaluar los resultados del aprendizaje cuya implementación prevé el uso de tecnologías de aprendizaje electrónico y a distancia. La importancia práctica del estudio radica en las particularidades de la formación de los estudiantes, futuros profesionales de la cultura y el arte, en la transición a la enseñanza a distancia. Este artigo apresenta a organização ...